Electrical Conductivity of Polyvinyl Alcohol Films filled with Multiwall Carbon Nanotubes (Journal of the College of Basic Education, 2023)
Efficient and inexpensive ways for the preparation of conductive PVAFilms were developed via a simple solution dispersion method. Multiwall carbon nanotube was used as filler in this research to achieve conductivity in PVA films. Well dispersion was achieved with the PVA solution. The conductivity increased from 10-13(Ω-cm)-1 to 9x10-12 (Ω-cm)-1 with filling ratio 3wt% and 6wt%. High conductivity was achieved at 12%; it reached 8.7x 10-4(Ω-cm)-1. The activation energy was decreased with ratios 3% and 6% and it became negative at 12wt% which indicates a metallic behavior of the films.